The Effectiveness of Brain-Based, Mindful, and Attachment-Based Parenting Training on Parental Orientation of Students with Social Anxiety Symptoms - Karimi, Hossein; Latifi, Zohreh; Yousefi , Zahra (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of this study was to compare the effectiveness of attachment-based, brain-based, and mindful parenting training on the parental orientation of mothers of students with social anxiety symptoms. Methods and Materials: The research method was a quasi-experimental design with a pre-test, post-test, and follow-up with three groups. The statistical population consisted of all mothers with elementary school children. The sample included 60 mothers from the city of Felard, selected purposefully based on inclusion and exclusion criteria, and assigned to three training groups and one control group. The research instrument was the Parental Orientation Scale (Yousefi, 2021). While the control group was on a waiting list, the experimental groups received the educational interventions. The collected data were analyzed at two levels: descriptive (mean and standard deviation) and inferential (repeated measures analysis of variance). Calculations were performed using SPSS software. Findings: The results showed that brain-based and attachment-based parenting had a significant effect on parental orientation, but attachment-based parenting did not significantly affect mothers’ orientation and could improve it. Conclusion: Thus, it can be concluded that brain-based and mindful parenting methods are effective in improving the mentioned parental constructs.